Diet at intestinal diseases: traditional bases and new discoverings - Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present the basic concept of dietetic therapy at bowel diseases, as well as the prospects of its improvement by addition of the specific components decreasing intestinal permeability.Original positions. In modern medicine dietetic therapy is still of value. In the last years essential progress was achieved for diet at diabetes mellitus, peptic ulcer and liver failure. Principles of dietetic therapy at bowel diseases as a whole remain unchanged and are based on the concept of mechanical and chemical sparing during relapse with gradual transition to general diet along with symptom regression. Issues on necessity of complete avoidance of lactose and gluten at «non-gluten» diseases of intestine are still disputable. It was demonstrated, that some components of food, in particular glutamine, omega-3-non-saturated fatty acids, zinc, selenium, curcumine, meletin, in an essential degree promote restoration of mucosal integrity and decrease intestinal permeability. Now these substances became obligatory components of enteric feeding mixtures. Development of alimentary additives and drugs on their basis is going on. Application of pre- and probiotics for stimulation of regeneration and development of functional nutrition products on their basis invokes major interest.Conclusion. Investigations of methods to reveal those components of food which can have the concealed damaging effect or, on the contrary, to sustain integrity of a mucosa, is still in the progress as well as development of the drugs, food additives and functional nutrition components, which can be applied as addition to traditional diet and promote decrease of intestinal permeability.